Evaluation and redesign of the primers for detecting nitrogen cycling genes in environments. Issue 9 (25th July 2022) - Wang, Zhujun; Feng, Kai; Wei, Ziyan; Wu, Yueni; Isobe, Kazuo; Senoo, Keishi; Peng, Xi; Wang, Danrui; He, Qing; Du, Xiongfeng; Li, Shuzhen; Li, Yan; et al.
Abstract: A better understanding of how nitrogen (N) cycling genes are involved in ecological processes is one of the crucial areas of microbial ecology. Currently, most molecular biological techniques investigating N cycling genes in the environment heavily rely on the accuracy of the polymerase chain reaction (PCR) primers; however, their specificity and coverage have not been comprehensively evaluated. Here, we collected a sequence database, NcycFunGen, aimed for primer evaluation and redesign. NcycFunGen was based on hidden Markov model profiles for 22 marker genes involved in N cycling, which included 607, 359 paired nucleotide and protein sequences with their taxonomic information. Then, a total of 608 published primers were fully evaluated through NcycFunGen, as well as against full‐length sequences collected from KEGG. The new primers were designed by DegePrime. In the experiment, the updated ureC gene primer pair ureC607F/ureC898R and nifH gene primer pair nifH107F64/nifH379R64 was applied to a urea amendment site using droplet digital PCR and high‐throughput amplicon sequencing. The results showed that the majority of primer pairs cover less than 30% sequences of target genes and that 22.55% were inappropriate for quantitative PCR and amplicon sequencing (<100 bp or >550 bp). In general, this in‐silico evaluation demonstrated that although many primers have been adopted in published studies, some of them should be validated and updated as needed according to the updated gene database. Therefore, new degenerate primer pairs for ureC targeting urease, bacterial and archaeal amoA targeting ammonium monooxygenase, and nifH targeting nitrogenase were designed through NcycFunGen. These new primer pairs showed higher coverage and amplification efficiency, as well as amplicon lengths that were applicable for high‐throughput amplicon sequencing. Furthermore, the experimental results displayed better characteristics than commonly used published ureC and nifH gene primer pairs. In conclusion, primer evaluation and redesign are highly recommended to improve the accuracy of primers targeting N cycling genes, which could facilitate amplicon‐based N cycling studies in various environments. The bioinformatics framework developed in this study can also be applied to build functional gene databases for other biogeochemical pathways. 摘要: 如何更好地理解氮循环功能基因在生态过程中的作用是微生物生态学的一个重要领域。目前，对环境中氮循环功能基因的分子生物学研究大多依赖于PCR引物的准确性，但这些引物的特异性和覆盖度尚未得到综合评价。本文中，我们构建了一个序列数据库NcycFunGen，旨在对引物进行评价和重新设计。 NcycFunGen基于HMM模型(hidden Markov model)，包含了22个涉及N循环的标记基因，总共包含607, 359条核苷酸和蛋白质序列及其分类信息。通过NcycFunGen以及从KEGG中收集的全长序列对已发表的608条引物进行评价。引物设计由DegePrime完成。实验中，通过数字定量PCR和高通量扩增子测序，将新设计的 ureC 基因引物对ureC607F/ureC898R和 nifH 基因引物对nifH107F64/nifH379R64应用于尿素添加实验。 结果表明，绝大多数引物对的覆盖度小于30%，22.55%的引物对的扩增长度不适用于定量PCR和扩增子测序(<100 bp或 > 550 bp)。引物评价结果表明，尽管许多前人研究中采用了许多引物，但其中一些引物需要根据更新的基因数据库进行验证和更新。因此，通过NcycFunGen设计了针对 ureC 基因、氨单加氧酶的细菌和古菌 amoA 基因和固氮基因 nifH 的新引物对。这些新引物对具有更高的覆盖度和扩增效率，以及扩增子长度适用于高通量扩增子测序。验证实验结果表明，新设计的 ureC 和 nifH 基因引物对比之前研究中常用的引物对具有更好的表现。 综上所述，建议对引物进行评价和重新设计，以提高针对氮循环功能基因引物的准确性，这样可为在不同环境中进行氮循环功能基因研究提供依据。本研究建立的生物信息学框架也可用于其他生物地球化学通路的功能基因数据库的构建。